Ancient but Not Forgotten: New Insights Into MPEG1, a Macrophage Perforin-Like Immune Effector - Bayly-Jones, Charles; Pang, Siew Siew; Spicer, Bradley A.; Whisstock, James C.; Dunstone, Michelle A. (Frontiers in Immunology, 2020)
Macrophage-expressed gene 1 (MPEG1/Perforin-2 [PRF2]) is an ancient metazoan protein belonging to the Membrane Attack Complex / Perforin (MACPF) branch of the MACPF/ Cholesterol Dependent Cytolysin (CDC) superfamily of pore forming proteins (PFPs). MACPF/CDC proteins are a large and extremely diverse superfamily that form large transmembrane aqueous channels in target membranes. In humans, MACPFs have known roles in immunity and development. Like perforin (PRF) and the membrane attack complex (MAC), MPEG1 is also postulated to perform a role in immunity. Indeed, bioinformatic studies suggest that gene duplications of MPEG1 likely gave rise to PRF and MAC components. Studies reveal partial or complete loss of MPEG1 causes an increased susceptibility to microbial infection in both cells and animals. To this end, MPEG1 expression is upregulated in response to proinflammatory signals such as tumour necrosis factor α (TNFα) and lipopolysaccharides (LPS). Furthermore, germline mutations in MPEG1 have been identified in connection with recurrent pulmonary mycobacterial infections in humans. Structural studies on MPEG1 revealed that it can form oligomeric pre-pores and pores. Strikingly, the unusual domain arrangement within the MPEG1 architecture suggests a novel mechanism of pore formation that may have evolved to guard against unwanted lysis of the host cell. Collectively, the available data suggest that MPEG1 likely functions as an intracellular pore-forming immune effector. Herein, we review the current understanding of MPEG1 evolution, regulation, and function. Furthermore, recent structural studies of MPEG1 are discussed, including the proposed mechanisms of action for MPEG1 bactericidal activity. Lastly limitations, outstanding questions and implications of MPEG1 models are explored in the context of the broader literature and in light of newly available structural data.